Influence of bacterial lectins on some reactions of nonspecific immunity in sarcoma 37 transplanted mice - Tanasienko, O.A.; Rudyk, M.P.; Pozur, V.V.; Potebnya, G.P. (Experimental Oncology, 2010)
The aim of this paper is to study preventive effect of cytotoxic lectin from Bacillus subtilis B-7025 on the tumor growth and nonspecific immunity in sarcoma 37 transplanted mice.